Bile cultures are poor predictors of antibiotic resistance in postoperative infections following pancreaticoduodenectomy. Issue 7 (July 2020) - Maxwell, Daniel W.; Jajja, Mohammad Raheel; Ferez-Pinzon, Anyul; Pouch, Stephanie M.; Cardona, Kenneth; Kooby, David A.; Maithel, Shishir K.; Russell, Maria C.; Sarmiento, Juan M.
Abstract: Background: Bile cultures (BC) have routinely been used to guide empiric antibiotic therapy for developing postoperative infections. The ability of BCs to predict sensitivity and resistance patterns (SRP) of site of infection cultures (SOIC) remains controversial. The aim was to assess the concordance of pathogens and SRPs between paired BC/SOICs. Methods: Medical records of consecutive patients undergoing pancreaticoduodenectomy were reviewed between 2014 and 2018. BC/SOIC pathogens and SRPs were compared on a patient-by-patient basis and concordance (K) was assessed. Results: Common patient characteristics of 522 included patients were 65-years-old, Caucasian (75.5%), male (54.2%), malignant indication (79.3%), and preoperative biliary stent (59.0%). Overall, 275 (89.6%) BCs matured identifiable isolates with 152 (55.2%) demonstrating polymicrobial growth. Ninety-two (17.6%) SOICs were obtained: 48 and 44 occurred in patients with and without intraoperative BCs. Stents were associated with bacteriobilia (85.7%, K = 0.947, p < 0.001; OR 22.727, p < 0.001), but not postoperative infections (15.2%; K = 0.302, p < 0.001; OR 1.428, p = 0.122). Forty-eight patients demonstrated paired BC/SOICs to evaluate. Pathogenic concordance of this group was 31.1% (K = 0.605, p < 0.001) while SRP concordance of matched pathogens was 46.7% (K = 0.167, p = 0.008). Conclusion: Bile cultures demonstrate poor concordance with the susceptibility/resistance patterns of postoperative infections following pancreaticoduodenectomy and may lead to inappropriate antibiotic therapies.